Lithium ion battery positive electrode material, preparation method thereof and lithium ion battery

CN123017945APending Publication Date: 2026-10-30GUIZHOU CNGR XINGYANG ENERGY STORAGE TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611344345.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

然而,这类材料普遍存在本征电子导电性差、锂离子扩散动力学缓慢的问题,导致高倍率工况下极化显著增加;同时,循环过程中过渡金属离子(Fe2+、Mn2+)易在电解液中溶出,进而与电解液发生副反应,加速界面劣化与容量衰减

Benefits of technology

本申请正极材料同时包括共轭导电聚合物包覆层和含钴材料包覆层,共轭导电聚合物具有连续π电子共轭结构,可快速传导电子;而且共轭导电聚合物中的极性位点可与内核表面强配位,锚定过渡金属离子。该材料在显著提升正极材料电子电导率的同时,可抑制过渡金属离子的溶出,并减少与电解液的副反应。含钴材料包括钴的氧化物和钴的羟基化合物,其中,钴的氧化物提供高电导与结构支撑;钴的羟基化合物富含羟基,可钝化正极材料表面缺陷、抑制颗粒团聚;两者在功能上互相配合,而且,两相原位共生形成异质结,降低离子传输势垒,促进锂离子扩散。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017945A_ABST
    Figure CN123017945A_ABST
Patent Text Reader

Abstract

The application provides a lithium ion battery positive electrode material, a preparation method thereof and a lithium ion battery, and relates to the field of lithium ion batteries. The lithium ion battery positive electrode material comprises a core, a first coating layer and a second coating layer which at least partially coat the core; the core comprises a lithium-containing phosphate positive electrode material; the first coating layer and the second coating layer are independently selected from a conjugated conductive polymer or a cobalt-containing material, and the material of the first coating layer is different from that of the second coating layer; wherein the cobalt-containing material comprises an oxide of cobalt and a hydroxyl compound of cobalt. The positive electrode material of the application simultaneously comprises a conjugated conductive polymer coating layer and a cobalt-containing material coating layer, the composite coating structure can effectively inhibit the dissolution of transition metal ions, optimize the transmission kinetics of electrons and lithium ions, improve the powder dispersibility and processing performance, thereby significantly improving the material compaction density, reducing the powder resistivity and reducing the irreversible capacity loss.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of lithium-ion batteries, and more particularly to a lithium-ion battery cathode material, its preparation method, and a lithium-ion battery. Background Technology

[0002] Olivine-type phosphate cathode materials, represented by lithium iron phosphate, lithium manganese iron phosphate, and their doped and modified systems, have become one of the mainstream cathode materials in the power and energy storage fields due to their low cost and stable structure. However, these materials generally suffer from poor intrinsic electronic conductivity and slow lithium-ion diffusion kinetics, leading to a significant increase in polarization under high-rate operating conditions; at the same time, transition metal ions (Fe2+) are also present during cycling. 2+ Mn 2+ Olivine phosphate cathode materials are prone to dissolution in electrolytes, leading to side reactions that accelerate interface degradation and capacity decay. Improving the electronic conductivity of olivine phosphate cathode materials while effectively suppressing transition metal ion dissolution and preventing particle agglomeration and adhesion are pressing technical challenges in the lithium-ion battery field. Summary of the Invention

[0003] The purpose of this application is to provide a lithium-ion battery cathode material, a method for preparing the same, and a lithium-ion battery, in order to solve the above-mentioned problems.

[0004] To achieve the above objectives, this application adopts the following technical solution: A lithium-ion battery cathode material, the lithium-ion battery cathode material comprising a core and a first coating layer and a second coating layer that at least partially cover the core; The core includes a lithium phosphate cathode material; The first coating layer and the second coating layer are independently selected from conjugated conductive polymers or cobalt-containing materials, and the materials of the first coating layer and the second coating layer are different. The cobalt-containing material includes cobalt oxides and cobalt hydroxy compounds.

[0005] In some embodiments, the general chemical formula of the lithium phosphate cathode material is LiFe. 1-x-y Mn x M y PO4, wherein 0 ≤ x ≤ 0.8, 0 ≤ y ≤ 0.15, and 1 - xy > 0; M includes at least one of Mg, Al, Ti, Zr, Ni, Co, Nb, and V; And / or, the conjugated conductive polymer includes at least one of polypyrrole, polyaniline, polythiophene, polycarbazole, and conjugated polyvinyl chloride; And / or, the cobalt oxide includes at least one of Co3O4 and CoO; And / or, the cobalt hydroxyl compound includes at least one of CoOOH and Co(OH)2; And / or, the mass of the conjugated conductive polymer accounts for 1.0% to 2.0% of the mass of the core; And / or, the mass of cobalt in the cobalt-containing material accounts for 0.2% to 0.6% of the mass of the core; And / or, the particle size of the kernel is 0.1~4.5μm.

[0006] In some embodiments, the BET of the lithium-ion battery cathode material is 8-30 m. 2 / g; And / or, the compaction density of the lithium-ion battery cathode material is 2.1-2.56 g / cm³. 3 ; And / or, the powder resistivity of the lithium-ion battery cathode material is 10-300 Ω·cm; And / or, the Dv50 of the lithium-ion battery cathode material is 0.1~5.0 μm; And / or, the Span of the lithium-ion battery cathode material is 1.0-7.0.

[0007] This application also provides a method for preparing a lithium-ion battery cathode material, including: Provide a lithium phosphate cathode material matrix; The lithium phosphate cathode material matrix is ​​mixed with a first coating agent and subjected to a first sintering to obtain an intermediate. The intermediate is mixed with the second coating agent and subjected to a second sintering to obtain the lithium-ion battery cathode material. Wherein, the first coating agent and the second coating agent are independently selected from polymer precursors or cobalt-containing precursors, and the first coating agent and the second coating agent are different; The cobalt-containing precursor includes Co(OH)2, or a mixture of cobalt oxide and CoOOH, wherein the cobalt oxide includes at least one of Co3O4 and CoO.

[0008] In some embodiments, the polymer precursor accounts for 1.0% to 2.0% of the mass of the lithium phosphate cathode material matrix; And / or, the mass percentage of cobalt in the cobalt-containing precursor is 0.2% to 0.6% of the mass of the lithium phosphate cathode material matrix; And / or, the polymer precursor includes polyvinyl chloride; And / or, the polymer precursor includes at least one of pyrrole, aniline, thiophene, and carbazole.

[0009] In some embodiments, the preparation method satisfies at least one of the following conditions: A. When the first coating agent or the second coating agent is a polymer precursor, the preparation method includes: The polymer precursor is mixed with a solvent to obtain a solution containing the polymer precursor; The solution containing the polymer precursor is mixed with the lithium phosphate cathode material matrix or the intermediate and then dried, subjected to a first sintering or a second sintering to obtain an intermediate or lithium-ion battery cathode material with a polymer coating on its surface; optionally, the first sintering or the second sintering includes: raising the temperature to 200-400°C at a rate of 2-10°C / min and holding it at that temperature for 4-10 hours. B. When the first coating agent or the second coating agent is a polymer precursor, the preparation method includes: The polymer precursor is mixed with an initiator, the lithium phosphate cathode material matrix or the intermediate, and an in-situ polymerization reaction is carried out to form a polymer reactant. The polymer reactants are washed, dried, and then subjected to a first sintering or a second sintering to obtain an intermediate or lithium-ion battery cathode material with a polymer coating on its surface; optionally, the first sintering or the second sintering includes: raising the temperature to 200-400°C at a rate of 2-10°C / min and holding it at that temperature for 4-10 hours. C. When the first coating agent or the second coating agent is Co(OH)2, the first sintering or the second sintering includes: raising the temperature to 130℃~250℃ at a heating rate of 2~5℃ / min and holding it at that temperature for 1~2h; then raising the temperature to 250℃~400℃ at a heating rate of 2~5℃ / min and holding it at that temperature for 2~4h. D. When the first coating agent or the second coating agent is a mixture of cobalt oxide and CoOOH, the first sintering or the second sintering includes: raising the temperature to 200-250°C at a heating rate of 2-5°C / min, holding at the temperature for 2-4 hours, and the mass ratio of cobalt oxide to CoOOH is (0.4~2.0):1.

[0010] In some embodiments, the solvent includes at least one of tetrahydrofuran, dimethyl sulfoxide, cyclohexanone, dimethylformamide, methyl isobutyl ketone, and N-methylpyrrolidone; And / or, the pH of the system is 1 to 3 when the in-situ polymerization reaction is carried out; And / or, the initiator includes at least one of ammonium persulfate, potassium persulfate, and sodium persulfate; And / or, the mass ratio of the initiator to the polymer precursor is (0.3~1.2):1; And / or, the in-situ polymerization reaction is carried out at a temperature of 5-35°C for a time of 2-7 hours.

[0011] In some embodiments, the method for preparing the lithium phosphate cathode material matrix includes: A slurry is obtained by mixing lithium source, iron source, phosphorus source, carbon source and water; The slurry was spray-dried to obtain precursor powder; The precursor powder is subjected to a third sintering process to obtain a lithium phosphate cathode material matrix.

[0012] In some embodiments, the method for preparing the lithium phosphate cathode material matrix satisfies at least one of the following conditions: (1) The lithium source includes at least one of lithium carbonate, lithium dihydrogen phosphate, and lithium hydroxide; (2) The iron source includes at least one of ferric phosphate, ferric manganese phosphate, ferrous oxalate, ferric oxide, ferrous sulfate, and ferric nitrate; (3) The phosphorus source includes at least one of iron phosphate, lithium dihydrogen phosphate, ammonium dihydrogen phosphate, and phosphoric acid; (4) The carbon source includes at least one of glucose, polyethylene glycol, sucrose, and citric acid; (5) The mass of the carbon source accounts for 5-16% of the total mass of the iron source and the phosphorus source; (6) The D50 of the slurry is 0.3~2.5μm; (7) The inlet air temperature of the spray dryer is 230-270℃ and the outlet air temperature is 90-110℃; (8) The third sintering is carried out under nitrogen protection, and the third sintering includes: raising the temperature to 650~820℃ at a heating rate of 1~5℃ / min and holding it for 6~15h; (9) The slurry further includes a manganese source, wherein the manganese source is selected from at least one of manganese ferric phosphate, manganese dioxide, manganese tetroxide, manganese phosphate, and manganese carbonate; (10) The slurry further includes an M source, which includes at least one of Mg source, Al source, Ti source, Zr source, Ni source, Co source, Nb source and V source.

[0013] This application also provides a lithium-ion battery, including the lithium-ion battery cathode material described above or including the lithium-ion battery cathode material prepared by the preparation method described above.

[0014] This application also provides an electrical device, including the lithium-ion battery described above.

[0015] Compared with the prior art, the beneficial effects of this application include: The cathode material of this application comprises both a conjugated conductive polymer coating layer and a cobalt-containing material coating layer. The conjugated conductive polymer has a continuous π-electron conjugated structure, enabling rapid electron conduction; moreover, the polar sites in the conjugated conductive polymer can strongly coordinate with the core surface, anchoring transition metal ions. This material significantly improves the electronic conductivity of the cathode material while suppressing the dissolution of transition metal ions and reducing side reactions with the electrolyte. The cobalt-containing material includes cobalt oxides and cobalt hydroxyl compounds. The cobalt oxides provide high conductivity and structural support; the cobalt hydroxyl compounds are rich in hydroxyl groups, which can passivate surface defects of the cathode material and inhibit particle aggregation. The two phases function synergistically, and the in-situ coexistence of the two phases forms a heterojunction, reducing the ion transport barrier and promoting lithium-ion diffusion.

[0016] This composite coating structure can effectively suppress the dissolution of transition metal ions in the cathode material, optimize electron and lithium ion transport dynamics, improve powder dispersibility and processing performance, thereby increasing the material compaction density, reducing powder resistivity, and reducing irreversible capacity loss. Attached Figure Description

[0017] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments will be briefly described below. It should be understood that the following drawings only show some embodiments of this application and should not be regarded as a limitation on the scope of this application.

[0018] Figure 1 The following are XRD comparison diagrams of the sintered products (CoOOH / Co3O4) of CoOOH, Co3O4, and Co(OH)2. Figure 1 The CoOOH / Co3O4 mentioned refers to the product generated by two-stage sintering of Co(OH)2; Figure 2 The XRD patterns of lithium iron phosphate (matrix) in Example 1, cathode material in Example 1, and cathode material in Example 5 are shown. Figure 3 The image shows a SEM image of lithium iron phosphate (matrix), the product from step one of Example 1. Figure 4 SEM image of the lithium-ion battery cathode material CoOOH / Co3O4@CPVC@LiFePO4 prepared in Example 1; Figure 5 This is a selected area SEM-EDS image of the lithium-ion battery cathode material CoOOH / Co3O4@CPVC@LiFePO4 in Example 1; Figure 6 EDS surface scan elemental distribution (O, P, Fe, Co, Cl, Ti) of the lithium-ion battery cathode material CoOOH / Co3O4@CPVC@LiFePO4 in Example 1. Figure 7 The full-cell cycle capacity retention curves for Example 1, Comparative Example 3, and Comparative Example 4 within the voltage range of 2.0-3.65V are shown. Detailed Implementation

[0019] As used in this article: "Prepared from" is synonymous with "comprising". The terms "comprising", "including", "having", "containing", or any other variations thereof as used herein are intended to cover non-exclusive inclusion. For example, a composition, step, method, article, or apparatus that includes the listed elements is not necessarily limited to those elements, but may include other elements not expressly listed or elements inherent to such composition, step, method, article, or apparatus.

[0020] The conjunction "composed of..." excludes any unspecified elements, steps, or components. If used in a claim, this phrase makes the claim closed, excluding materials other than those described, except for associated conventional impurities. When the phrase "composed of..." appears in a clause of the body of a claim rather than immediately following it, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0021] When a quantity, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pair of any upper or preferred value with any lower or preferred value, regardless of whether the range is disclosed individually. For example, when the range “1–5” is disclosed, the described range should be interpreted as including ranges “1–4”, “1–3”, “1–2”, “1–2 and 4–5”, “1–3 and 5”, etc. When numerical ranges are described herein, unless otherwise stated, the range is intended to include its endpoints and all integers and fractions within that range.

[0022] "And / or" is used to indicate that one or both of the described situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0023] A lithium-ion battery cathode material, the lithium-ion battery cathode material comprising a core and a first coating layer and a second coating layer that at least partially cover the core; The core includes a lithium phosphate cathode material; The first coating layer and the second coating layer are independently selected from conjugated conductive polymers or cobalt-containing materials, and the materials of the first coating layer and the second coating layer are different. The cobalt-containing material includes cobalt oxides and cobalt hydroxy compounds.

[0024] Conjugated conductive polymers possess a continuous π-electron conjugated structure, enabling rapid electron conduction. These polymers can construct continuous π-electron conductive channels on the core surface, replacing traditional carbon coating for interface modification. Their polar groups can also coordinate with the material surface, effectively inhibiting the dissolution of transition metal ions. However, single-phase conjugated conductive polymer coatings still suffer from limitations such as insufficient structural rigidity and a lack of anti-agglomeration hydroxyl sites. Cobalt oxides provide high conductivity and structural support, but lack active hydroxyl groups on the surface, making it difficult to inhibit particle sintering and adhesion, resulting in limited interface passivation. Cobalt hydroxyl compounds are rich in hydroxyl groups, which can passivate surface defects and inhibit particle agglomeration, but their intrinsic conductivity is insufficient to meet the requirements for efficient interface transport. Cobalt-containing materials include both cobalt oxides and cobalt hydroxyl compounds, allowing for complementary advantages: cobalt oxides provide high electron conductivity channels and structural support, while cobalt hydroxyl compounds provide surface hydroxyl sites to inhibit agglomeration and passivate interface defects. Simultaneously, the heterojunction formed by the two phases can accelerate lithium-ion transport, thus solving the problem of insufficient functionality in single-phase cobalt materials. The in-situ coexistence of two phases forms a heterojunction, reducing the ion transport barrier. The coating layer of the cathode material in this application includes both a conjugated conductive polymer and a cobalt-containing material. The two work together to achieve a complementary effect. The conjugated conductive polymer layer is responsible for conductivity and dissolution inhibition, while the cobalt-containing material layer is responsible for blocking the electrolyte, dispersing particles, and strengthening the structure, thus achieving simultaneous improvement in multiple properties.

[0025] It should be noted that the coating order of the first coating layer and the second coating layer along the radial direction of the lithium-ion battery cathode material is interchangeable. That is, the first coating layer can be located inside or outside the second coating layer. Both coating orders can achieve the technical effects of this application.

[0026] In some embodiments, the lithium-ion battery cathode material consists of, from the inside out, a lithium phosphate cathode material, a conjugated conductive polymer, and a cobalt-containing material; or the lithium-ion battery cathode material consists of, from the inside out, a lithium phosphate cathode material, a cobalt-containing material, and a conjugated conductive polymer.

[0027] In some embodiments, the general chemical formula of the lithium phosphate cathode material is LiFe. 1-x-y Mn x M y PO4, wherein 0≤x≤0.8, 0≤y≤0.15, and 1-xy>0; M includes at least one of Mg, Al, Ti, Zr, Ni, Co, Nb, and V; the above-mentioned lithium-containing phosphate cathode material is an olivine-type phosphate cathode material. The cathode material of this application is compatible with lithium iron phosphate, lithium manganese iron phosphate, and their doped and modified systems, and has broad application prospects.

[0028] In some embodiments, the conjugated conductive polymer includes at least one of polypyrrole, polyaniline, polythiophene, polycarbazole, and conjugated polyvinyl chloride (CPVC); The polar Cl sites in conjugated polyvinyl chloride can strongly coordinate with Fe-O and PO bonds on the LFP surface, anchoring Fe. 2+ This coating not only significantly improves the electronic conductivity of the material, but also effectively inhibits the dissolution of transition metals and reduces electrolyte side reactions.

[0029] In some embodiments, the cobalt oxide includes at least one of Co3O4 and CoO; In some embodiments, the cobalt hydroxyl compound includes at least one of CoOOH and Co(OH)2; In some embodiments, the mass of the conjugated conductive polymer accounts for 1.0% to 2.0% of the mass of the core; for example, the mass of the conjugated conductive polymer accounts for 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0% or any value between 1.0% and 2.0% of the mass of the core.

[0030] In some embodiments, the mass of cobalt in the cobalt-containing material accounts for 0.2% to 0.6% of the mass of the core; for example, the mass of cobalt in the cobalt-containing material accounts for any value between 0.2%, 0.3%, 0.4%, 0.5%, 0.6% or 0.2% to 0.6% of the mass of the core.

[0031] In some embodiments, the kernel particle size is 0.1~4.5μm; for example, the kernel particle size is 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.8μm, 1μm, 1.3μm, 1.5μm, 1.8μm, 2.0μm, 3.0μm, 4.0μm, 4.5μm or any value between 0.1~4.5μm.

[0032] In some embodiments, the BET of the lithium-ion battery cathode material is 8-30 m. 2 / g; for example, the BET of lithium-ion battery cathode materials is 8 m 2 / g、10 m 2 / g、13 m 2 / g、15 m 2 / g、18 m 2 / g、20 m 2 / g、23 m 2 / g、25 m 2 / g、28m 2 / g、30 m 2 / g or 8-30 m 2 Any value between / g.

[0033] In some embodiments, the compaction density of the lithium-ion battery cathode material is 2.1-2.56 g / cm³. 3 For example, the compaction density of lithium-ion battery cathode material is 2.1 g / cm³. 3 2.2 g / cm 3 2.3 g / cm 3 2.4 g / cm 3 2.5 g / cm 3 2.56 g / cm 3 Or 2.1-2.56 g / cm³ 3 Any value between.

[0034] In some embodiments, the powder resistivity of the lithium-ion battery cathode material is 10-300 Ω·cm; for example, the powder resistivity of the lithium-ion battery cathode material is any value between 10 Ω·cm, 30 Ω·cm, 50 Ω·cm, 80 Ω·cm, 100 Ω·cm, 130 Ω·cm, 150 Ω·cm, 180 Ω·cm, 200 Ω·cm, 230 Ω·cm, 250 Ω·cm, 280 Ω·cm, 300 Ω·cm, or 10-300 Ω·cm.

[0035] In some embodiments, the Dv50 of the lithium-ion battery cathode material is 0.1~5.0 μm; for example, the Dv50 of the lithium-ion battery cathode material is 0.1 μm, 0.3 μm, 0.5 μm, 0.8 μm, 1 μm, 1.3 μm, 1.5 μm, 1.8 μm, 2 μm, 3 μm, 4 μm, 5 μm or any value between 0.1 and 5.0 μm.

[0036] In some embodiments, the Span of the lithium-ion battery cathode material is 1.0-7.0. For example, the Span of the lithium-ion battery cathode material is 1.0, 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, or any value between 1.0 and 7.0.

[0037] This application also provides a method for preparing a lithium-ion battery cathode material, including: Provide a lithium phosphate cathode material matrix; The lithium phosphate cathode material matrix is ​​mixed with a first coating agent and subjected to a first sintering to obtain an intermediate. The intermediate is mixed with the second coating agent and subjected to a second sintering to obtain the lithium-ion battery cathode material. Wherein, the first coating agent and the second coating agent are independently selected from polymer precursors or cobalt-containing precursors, and the first coating agent and the second coating agent are different; The cobalt-containing precursor includes Co(OH)2, or a mixture of cobalt oxide and CoOOH, wherein the cobalt oxide includes at least one of Co3O4 and CoO.

[0038] In some embodiments, the mass of the polymer precursor accounts for 1.0% to 2.0% of the mass of the lithium phosphate cathode material matrix; for example, the mass of the polymer precursor accounts for any value between 1.0%, 1.3%, 1.5%, 1.8%, 2% or 1.0% to 2.0% of the mass of the lithium phosphate cathode material matrix.

[0039] In some embodiments, the mass of cobalt in the cobalt-containing precursor accounts for 0.2% to 0.6% of the mass of the lithium phosphate cathode material matrix; for example, the mass of cobalt in the cobalt-containing precursor accounts for any value between 0.2%, 0.3%, 0.4%, 0.5%, 0.6% or 0.2% to 0.6% of the mass of the lithium phosphate cathode material matrix.

[0040] In some embodiments, the polymer precursor comprises polyvinyl chloride; In some embodiments, the polymer precursor includes at least one of pyrrole, aniline, thiophene, and carbazole.

[0041] In some embodiments, when the first coating agent or the second coating agent is a polymer precursor (e.g., polyvinyl chloride, PVC), the preparation method includes: The polymer precursor is mixed with a solvent to obtain a solution containing the polymer precursor; The solution containing the polymer precursor is mixed with the lithium phosphate cathode material matrix or the intermediate, and then dried, subjected to a first sintering or a second sintering to obtain an intermediate or lithium-ion battery cathode material with a polymer coating on its surface. Optionally, the first sintering or the second sintering includes: raising the temperature to 200-400°C at a rate of 2-10°C / min and holding it at that temperature for 4-10 hours. For example, the heating rate of the first sintering or the second sintering is any value between 2°C / min, 5°C / min, 7°C / min, 10°C / min, or 2-10°C / min; the temperature of the second sintering is any value between 200°C, 230°C, 250°C, 280°C, 300°C, 330°C, 350°C, 380°C, 400°C, or 200-400°C; and the time of the second sintering is any value between 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, or 4-10 hours.

[0042] In some embodiments, drying is performed in a vacuum drying oven before the first or second sintering, and the drying includes drying at a temperature of 50-65°C for 12 hours under vacuum conditions to remove the solvent. For example, the drying temperature before the first or second sintering is any value between 50°C, 55°C, 60°C, 65°C, or 50-65°C.

[0043] In some embodiments, the first or second sintering is carried out under a nitrogen atmosphere. Under the first or second sintering conditions, polyvinyl chloride (PVC) can undergo a dehydrochlorination reaction, and the molecular backbone forms a π-electron conjugated structure with carbon-carbon double bonds, transforming into conjugated polyvinyl chloride (CPVC) with semiconductor properties. This CPVC is uniformly coated on the surface of the lithium phosphate cathode material matrix or intermediate, resulting in an intermediate or lithium-ion battery cathode material with a polymer coating on its surface.

[0044] In some embodiments, when the first coating agent or the second coating agent is a polymer precursor (e.g., aniline, pyrrole, thiophene, carbazole), the preparation method includes: The polymer precursor is mixed with an initiator, the lithium phosphate cathode material matrix or the intermediate, and an in-situ polymerization reaction is carried out to form a polymer reactant. The polymer reactants are washed, dried, and then subjected to a first sintering or a second sintering to obtain an intermediate or lithium-ion battery cathode material coated with a polymer. Optionally, the first sintering or the second sintering includes: raising the temperature to 200-400°C (e.g., 200°C, 230°C, 250°C, 280°C, 300°C, 330°C, 350°C, 380°C, 400°C, or any value between 200-400°C) at a rate of 2-10°C / min (e.g., 2°C / min, 5°C / min, 7°C / min, 10°C / min or any value between 200-400°C), and holding at that temperature for 4-10 hours (e.g., 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours). (h or any value between 4 and 10h); on the one hand, in-situ polymer growth achieves uniform and complete coating, constructs a continuous conductive network, reduces material resistivity, and improves rate performance; on the other hand, low-temperature sintering does not damage the positive electrode crystal structure, avoids lithium loss, and ensures high capacity and cycle stability.

[0045] In some embodiments, when the first coating agent or the second coating agent is Co(OH)2, the first sintering or the second sintering includes: raising the temperature to 130°C to 250°C (e.g., 130°C, 150°C, 180°C, 200°C, 230°C, 250°C, or any value between 2°C and 5°C) at a heating rate of 2 to 5°C / min (e.g., 2°C / min, 3°C / min, 4°C / min, 5°C / min, or any value between 2°C and 5°C), and holding at that temperature for 1 to 2 hours (e.g., 1 hour). Under these conditions, Co(OH)2 can be partially oxidized to CoOOH. Then, the temperature is increased to 250℃~400℃ (e.g., 250℃, 280℃, 300℃, 330℃, 350℃, 380℃, 400℃, or any value between 2 and 5℃ / min) at a heating rate of 2~5℃ / min, and held for 2~4 hours (e.g., 2 h, 3 h, 4 h, or any value between 2 and 4 h). Under these conditions, Co3O4 can continue to be generated. A CoOOH / Co3O4 coating layer can be formed through two-stage low-temperature sintering. In other words, the cobalt-containing material layer can be obtained in situ from Co(OH)2 through controlled oxidation and dehydration via segmented heat treatment. Furthermore, the cobalt-containing material layer formed by this method has a continuous, uniform coating and strong adhesion.

[0046] In some embodiments, when the first coating agent or the second coating agent is a mixture of cobalt oxide and CoOOH, the first sintering or the second sintering includes: raising the temperature to 200-250°C (e.g., 200°C, 230°C, 250°C, or any value between 200-250°C) at a heating rate of 2-5°C / min (e.g., 2°C / min, 3°C / min, 4°C / min, 5°C / min, or any value between 2 and 5°C / min), holding at that temperature for 2-4 h (e.g., 2 h, 3 h, 4 h, or any value between 2 and 4 h), and the mass ratio of cobalt oxide to CoOOH is (0.4-2.0):1 (e.g., 0.4:1, 1:1, 1.5:1, 2:1, or any value between 0.4-2.0):1).

[0047] In some embodiments, the solvent includes at least one of tetrahydrofuran, dimethyl sulfoxide, cyclohexanone, dimethylformamide, methyl isobutyl ketone, and N-methylpyrrolidone; In some embodiments, the pH of the system is 1 to 3 when the in-situ polymerization reaction is carried out; for example, the pH of the system is 1, 2, 3 or any value between 1 and 3 when the in-situ polymerization reaction is carried out.

[0048] In some embodiments, the initiator includes at least one selected from ammonium persulfate, potassium persulfate, and sodium persulfate; In some embodiments, the mass ratio of the initiator to the polymer precursor is (0.3~1.2):1; for example, the mass ratio of the initiator to the polymer precursor is any value between 0.3:1, 0.5:1, 0.7:1, 1:1, 1.2:1 or (0.3~1.2):1.

[0049] In some embodiments, the in-situ polymerization reaction is carried out at a temperature of 5-35°C for a duration of 2-7 hours. For example, the temperature of the in-situ polymerization reaction is any value between 5°C, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, or 5-35°C; the duration of the in-situ polymerization reaction is any value between 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, or 2-7 hours.

[0050] It should be noted that lithium phosphate cathode material substrates can be obtained by purchase or by preparation.

[0051] In some embodiments, the method for preparing the lithium phosphate cathode material matrix includes: A slurry is obtained by mixing lithium source, iron source, phosphorus source, carbon source and water; The slurry was spray-dried to obtain precursor powder; The precursor powder is subjected to a third sintering to obtain a lithium phosphate cathode material matrix. In some embodiments, the lithium source includes at least one of lithium carbonate, lithium dihydrogen phosphate, and lithium hydroxide; In some embodiments, the iron source includes at least one of ferric phosphate, ferric manganese phosphate, ferrous oxalate, ferric oxide, ferrous sulfate, and ferric nitrate. In some embodiments, the phosphorus source includes at least one of iron phosphate, lithium dihydrogen phosphate, ammonium dihydrogen phosphate, and phosphoric acid; In some embodiments, the carbon source includes at least one of glucose, polyethylene glycol, sucrose, and citric acid; In some embodiments, the carbon source accounts for 5-16% of the total mass of the iron source and the phosphorus source; this application optimizes the amount of carbon source added, while satisfying the Fe... 3+ Under the premise of reducing requirements and maintaining basic conductivity, the amount of carbon source added is reduced, avoiding defects such as particle adhesion and uneven coating caused by excessive carbon source pyrolysis.

[0052] For example, the mass of the carbon source accounts for 5%, 8%, 10%, 13%, 15%, 16% of the total mass of the iron and phosphorus sources, or any value between 5% and 16%.

[0053] In some embodiments, the D50 of the slurry is 0.3 to 2.5 μm; for example, the D50 of the carbon slurry is 0.3 μm, 0.5 μm, 0.7 μm, 1 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.8 μm, 2.0 μm, 2.5 μm or any value between 0.3 and 2.5 μm.

[0054] In some embodiments, the inlet air temperature of the spray dryer is 230-270°C and the outlet air temperature is 90-110°C; for example, the inlet air temperature of the spray dryer is any value between 230°C, 250°C, 270°C, or 230-270°C; the outlet air temperature of the spray dryer is any value between 90°C, 100°C, 110°C, or 90-110°C.

[0055] In some embodiments, the third sintering is carried out under nitrogen protection, and the third sintering includes: raising the temperature to 650-820°C at a heating rate of 1-5°C / min and holding it at that temperature for 6-15 hours.

[0056] For example, the heating rate of the third sintering is any value between 1℃ / min, 2℃ / min, 3℃ / min, 4℃ / min, 5℃ / min, or 1~5℃ / min; the temperature of the third sintering is any value between 650℃, 670℃, 700℃, 720℃, 750℃, 770℃, 800℃, 820℃, or 650~820℃; and the time of the third sintering is any value between 6 h, 8 h, 10 h, 13 h, 15 h, or 6~15 h. In some embodiments, the slurry further includes a manganese source selected from at least one of manganese ferric phosphate, manganese dioxide, manganese tetroxide, manganese phosphate, and manganese carbonate.

[0057] In some embodiments, the slurry further includes an M source, which includes at least one of a Mg source, an Al source, a Ti source, a Zr source, a Ni source, a Co source, a Nb source, and a V source.

[0058] This application also provides a lithium-ion battery, including the lithium-ion battery cathode material described above or including the lithium-ion battery cathode material prepared by the preparation method described above.

[0059] This application also provides an electrical device, including the lithium-ion battery described above.

[0060] The implementation schemes of this application will be described in detail below with reference to specific embodiments. However, those skilled in the art will understand that the following embodiments are only for illustrating this application and should not be regarded as limiting the scope of this application. Unless otherwise specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments used without specified manufacturers are all conventional products that can be purchased commercially.

[0061] Example 1 Example 1 provides a lithium-ion battery cathode material, the specific preparation method of which is as follows: Step 1: Preparation of the matrix (lithium iron phosphate); Lithium carbonate, iron phosphate, titanium dioxide, and carbon sources (glucose and PEG) were mixed. Specifically, the Li / P molar ratio was 1.006:1, the Ti doping amount was 3000 ppm based on the mass of iron phosphate, the glucose content was 7% of the mass of iron phosphate, and the PEG content was 3% of the mass of iron phosphate. Using deionized water as a solvent, the mixture was ground in a sand mill until the particle size D50 = 0.3 ± 0.01 μm, resulting in a mixed slurry. The slurry was spray-dried, with the inlet air temperature controlled at 250℃ and the outlet air temperature at 100℃, to obtain lithium iron phosphate precursor powder. The lithium iron phosphate precursor powder was sintered under a nitrogen atmosphere (oxygen content controlled < 50 ppm) at a heating rate of 3℃ / min to 760℃ for 12 h, and then cooled to room temperature to obtain lithium iron phosphate with a small amount of carbon coating. The sintered lithium iron phosphate was subjected to air jet milling with a grinding pressure of 0.5 MPa and a grading frequency of 50 Hz to control the particle size D50 of lithium iron phosphate to 1.2 μm, thus obtaining the lithium iron phosphate matrix.

[0062] Step 2: Prepare the first coating layer (conjugated conductive polymer coating layer) to form the CPVC@LiFePO4 intermediate; 1.5 g of PVC (analytical grade polyvinyl chloride) was dissolved in 200 mL of tetrahydrofuran solvent and stirred at 40 °C for 30 min to form a PVC solution. 100 g of the lithium iron phosphate matrix prepared in step one was slowly added, and stirring continued for 2 h to allow the PVC to uniformly adhere to the lithium iron phosphate surface. The mixed slurry system was transferred to a vacuum drying oven and dried at 60 °C for 12 h to slowly remove the tetrahydrofuran solvent. The dried PVC@LiFePO4 powder was sintered under a nitrogen atmosphere at a heating rate of 2 °C / min to 270 °C and held for 8 h. This caused the PVC molecules to undergo a dehydrochlorination reaction, forming a continuous carbon-carbon double bond π-electron conjugated structure (CPVC). The sintered powder was passed through a 200-mesh vibrating sieve to remove a small amount of agglomerated particles, yielding the CPVC@LiFePO4 intermediate.

[0063] Step 3: Prepare the second coating layer (containing cobalt material layer) to form the final product CoOOH / Co3O4@CPVC@LiFePO4.

[0064] The CPVC@LiFePO4 intermediate obtained in step two was mixed with nano-sized Co(OH)2 powder, with the Co element in the Co(OH)2 accounting for 0.4% of the mass of the lithium iron phosphate matrix. The mixture was stirred at 2000 rpm for 30 min using a high-speed mixer to ensure uniform dispersion of Co(OH)2 on the surface of the intermediate. The mixed powder was then sintered in stages under air atmosphere. The temperature was increased to 150℃ at a rate of 5℃ / min and held for 1.5 h to generate CoOOH in situ. The temperature was then further increased to 300℃ at a rate of 5℃ / min and held for 3 h to generate Co3O4. These two stages of low-temperature sintering resulted in the in-situ formation of a CoOOH / Co3O4 coating layer. After natural cooling to room temperature, the product was passed through a 200-mesh vibrating sieve to obtain the final product, CoOOH / Co3O4@CPVC@LiFePO4 cathode material. The powder resistivity of this cathode material was measured to be 15.49 Ω·cm.

[0065] Figure 1 The images show a comparison of the XRD patterns of the sintered products of CoOOH, Co3O4, and Co(OH)2. Figure 1 The CoOOH / Co3O4 mentioned refers to the sintered product of Co(OH)2. The preparation method of the Co(OH)2 sintered product is as follows: Following the sintering conditions of Co(OH)2 in Example 1, Co(OH)2 is sintered in sections under air atmosphere. The temperature is increased to 150℃ at a rate of 5℃ / min and held for 1.5 hours; then, the temperature is further increased to 300℃ at a rate of 5℃ / min and held for 3 hours to obtain the Co(OH)2 sintered product. Figure 1 It can be seen that the characteristic peaks of CoOOH and Co3O4 appeared simultaneously in the sintered product of Co(OH)2, indicating that sintering Co(OH)2 according to the conditions of Example 1 can yield a product that simultaneously has CoOOH and Co3O4.

[0066] Figure 3 This is a SEM image of lithium iron phosphate, the product from step one of Example 1. Figure 4 This is a SEM image of the lithium-ion battery cathode material CoOOH / Co3O4@CPVC@LiFePO4 prepared in Example 1. Figure 3 and Figure 4It can be seen that the surface of the uncoated lithium iron phosphate matrix particles is smooth and the primary particle boundaries are clear; after CoOOH / Co3O4@CPVC coating modification, a thin composite coating layer is uniformly covered on the particle surface. At the same time, since CoOOH is rich in hydroxyl groups, it can effectively passivate particle surface defects and reduce interfacial adhesion between particles. Therefore, the particle dispersion of the coated sample is slightly improved compared with the matrix.

[0067] Figure 5 , Figure 6 SEM-EDS results for CoOOH / Co3O4@CPVC@LiFePO4. Elemental surface scan results ( Figure 6 The results showed that both Co and Cl elements were continuously and diffusely distributed without local clusters or enrichment, confirming that both the first coating layer (CPVC) and the second coating layer (CoOOH / Co3O4) were attached to the particle surface in the form of a uniform thin film. Fe, P, O, Co, Ti and trace Cl elements were detected simultaneously in the EDS spectrum. The stable detection of Cl further corroborated the existence of the CPVC conjugated polymer coating layer.

[0068] Example 2 Example 2 provides a lithium-ion battery cathode material. Example 2 is prepared using a method similar to that of Example 1. The difference from Example 1 is that in the preparation process of the CoOOH / Co3O4@CPVC@LiFePO4 cathode material, the amount of PVC in step two is adjusted to 1.0g, so that PVC accounts for 1.0% of the mass of the lithium iron phosphate matrix.

[0069] The test results showed that the resistivity of the positive electrode material in Example 2 was 52.14 Ω·cm.

[0070] Example 3 Example 3 provides a lithium-ion battery cathode material. Example 3 is prepared using a method similar to that of Example 1. The difference from Example 1 is that in the preparation process of the CoOOH / Co3O4@CPVC@LiFePO4 cathode material, the amount of PVC in step two is adjusted to 2.0g, so that PVC accounts for 2.0% of the mass of the lithium iron phosphate matrix.

[0071] The test results showed that the resistivity of the positive electrode material in Example 3 was 44.30 Ω·cm.

[0072] Example 4 Example 4 provides a lithium-ion battery cathode material. Example 4 is prepared using a method similar to that of Example 1. The difference from Example 1 is that in the preparation process of the CoOOH / Co3O4@CPVC@LiFePO4 cathode material, the amount of Co(OH)2 added in step three is adjusted, and the Co element in Co(OH)2 accounts for 0.2% of the mass of the lithium iron phosphate matrix.

[0073] Example 5 Example 5 provides a lithium-ion battery cathode material. Example 5 is prepared using a method similar to that of Example 1. The difference from Example 1 is that in the preparation process of the CoOOH / Co3O4@CPVC@LiFePO4 cathode material, the amount of Co(OH)2 added in step three is adjusted, and the Co element in Co(OH)2 accounts for 0.6% of the mass of the lithium iron phosphate matrix.

[0074] Figure 2 The XRD patterns of lithium iron phosphate (matrix) in Example 1, cathode material in Example 1, and cathode material in Example 5 are shown below. Figure 2 It can be seen that both the modified and unmodified samples maintained the characteristic peaks of the LiFePO4 olivine crystal form, indicating a stable matrix structure. As the Co coating content increased from 0.4% (Example 1) to 0.6% (Example 5), diffraction signals appeared at the positions corresponding to the CoOOH and Co3O4 standard cards in the cathode material samples and gradually increased, confirming the simultaneous presence of CoOOH and Co3O4 in the cathode material, with their content increasing with the increase of Co(OH)2 content. Furthermore, no characteristic peaks of cobalt phosphate, lithium cobalt phosphate, or other impurity phases appeared in the XRD patterns of the cathode materials of Examples 1 and 5, indicating that the Co component did not undergo an interfacial reaction with the LiFePO4 matrix during the coating process, and CoOOH / Co3O4 could stably exist on the material surface. Simultaneously, the conjugated conductive polymer coating layer (CPVC) had an amorphous structure and did not show obvious characteristic peaks, consistent with theoretical expectations. Preliminary confirmation indicates that the multilayer coated target cathode material has been successfully prepared.

[0075] Example 6 Example 6 provides a lithium-ion battery cathode material. Example 6 is prepared using a method similar to that of Example 1. The difference from Example 1 is that in the preparation process of the CoOOH / Co3O4@CPVC@LiFePO4 cathode material, the amount of PVC in step two is adjusted to 1.2g, so that PVC accounts for 1.2% of the mass of the lithium iron phosphate matrix; the amount of Co(OH)2 added in step three is adjusted, and the Co element in Co(OH)2 accounts for 0.3% of the mass of the lithium iron phosphate matrix.

[0076] Example 7 Example 7 provides a lithium-ion battery cathode material. Example 7 is prepared using a method similar to that of Example 1, except that conjugated polyvinyl chloride (CPVC) is replaced with polyaniline (PANI) to prepare a CoOOH / Co3O4@PANI@LiFePO4 cathode material.

[0077] Specifically, step two of Example 7 is adjusted to prepare the first coating layer (polyaniline PANI coating): a measured amount of deionized water and dilute hydrochloric acid are added to a container to adjust the pH of the system to 1-2. 1.5g of aniline monomer is added and stirred at 30°C for 40min to disperse completely. 100g of lithium iron phosphate cathode material is slowly added and stirred continuously for 2h to ensure that the aniline monomer molecules are uniformly attached to the surface of the lithium iron phosphate. An initiator ammonium persulfate aqueous solution is slowly added dropwise, with a mass ratio of ammonium persulfate to aniline monomer of 0.5:1. In-situ polymerization is carried out at a constant temperature of 30°C for 6h to form a polyaniline PANI conjugated conductive coating layer. After the reaction, the mixture is filtered and washed multiple times until the filtrate is neutral. It is then transferred to a vacuum drying oven and dried at 60°C for 12h. The dried PANI@LiFePO4 powder is sintered under a nitrogen atmosphere at a heating rate of 2°C / min to 200°C, held at that temperature for 6h, and then naturally cooled to obtain the PANI@LiFePO4 intermediate.

[0078] Example 8 Example 8 provides a lithium-ion battery cathode material. Example 8 is prepared using a method similar to that of Example 1, except that the second coating layer is replaced with a mixture of CoOOH and CoO to prepare a CoOOH / CoO@CPVC@LiFePO4 cathode material.

[0079] Specifically, step three of Example 8 is adjusted as follows: The CPVC@LiFePO4 intermediate obtained in step two is mixed with nano-sized CoOOH and nano-sized CoO powder (the total mass of Co element in CoOOH and CoO accounts for 0.4% of the mass of lithium iron phosphate, and the mass ratio of CoOOH to CoO is 1:1). The mixture is stirred at 2000 rpm for 30 min using a high-speed mixer to ensure that CoOOH and CoO are uniformly dispersed and loaded onto the surface of the intermediate. The mixed powder is sintered under a nitrogen atmosphere, heated to 250°C at a heating rate of 5°C / min, and held at that temperature for 4 h. After sintering, the mixture is naturally cooled to room temperature in the furnace, and the product is passed through a 200-mesh vibrating sieve to obtain the final product, CoOOH / CoO@CPVC@LiFePO4 cathode material.

[0080] Example 9 Example 9 provides a lithium-ion battery cathode material. Example 9 is prepared using a method similar to Example 1, except that: this example uses commercially available lithium manganese iron phosphate as the core matrix, with the chemical formula LiFe. 0.4 Mn 0.6 PO4.

[0081] Steps two and three follow the coating process exactly as described in Example 1, sequentially completing the CPVC coating and the CoOOH / Co3O4 coating, ultimately yielding CoOOH / Co3O4@CPVC@LiFe. 0.4 Mn 0.6 The cathode material for PO4.

[0082] Example 10 Example 10 provides a lithium-ion battery cathode material. Example 10 is prepared using a method similar to that of Example 1, except that the order of preparing the first coating layer and the second coating layer is reversed to prepare the CPVC@CoOOH / Co3O4@LiFePO4 cathode material.

[0083] Step 1: Completely the same as Step 1 in Example 1.

[0084] Step 2: Prepare the first coating layer (containing cobalt material layer) to form the CoOOH / Co3O4@LiFePO4 intermediate; Lithium iron phosphate (LiFePO4) and nano-sized Co(OH)2 powder were mixed at a Co content of 0.4% of LiFePO4 mass. The mixture was stirred at 2000 rpm for 30 min using a high-speed mixer to ensure uniform dispersion of Co(OH)2 on the surface of the LiFePO4 matrix. The mixed powder was then sintered in stages under air atmosphere. The temperature was increased to 150°C at a rate of 5°C / min and held for 1.5 h to generate CoOOH in situ. The temperature was then increased to 300°C at a rate of 5°C / min and held for 3 h, allowing the remaining Co(OH)2 to react and generate Co3O4. The two stages of low-temperature sintering resulted in the in-situ formation of a CoOOH / Co3O4 coating layer. After natural cooling to room temperature, the product was passed through a 200-mesh vibrating sieve to obtain the CoOOH / Co3O4@LiFePO4 intermediate.

[0085] Step 3: Prepare the second coating layer (conjugated conductive polymer coating) to form the final product CPVC@CoOOH / Co3O4@LiFePO4; 1.5 g of PVC (analytical grade polyvinyl chloride) was dissolved in 200 ml of tetrahydrofuran solvent and stirred at 40 °C for 30 min to form a PVC solution. 100 g of CoOOH / Co3O4@LiFePO4 intermediate was slowly added, and stirring continued for 2 h to allow PVC molecules to uniformly adhere to the intermediate surface. The mixed slurry system was transferred to a vacuum drying oven and dried at 60 °C for 12 h to slowly remove the tetrahydrofuran solvent. The dried PVC@CoOOH / Co3O4@LiFePO4 powder was sintered under a nitrogen atmosphere at a heating rate of 2 °C / min to 270 °C and held for 8 h. This caused the PVC molecules to undergo a dehydrochlorination reaction, forming a continuous carbon-carbon double bond π-electron conjugated structure (CPVC). The sintered powder was passed through a 200-mesh vibrating sieve to remove a small amount of agglomerated particles, yielding the CPVC@CoOOH / Co3O4@LiFePO4 cathode material.

[0086] The test results showed that the resistivity of the positive electrode material in Example 10 was 24.20 Ω·cm.

[0087] Comparative Example 1 Comparative Example 1 provides a lithium-ion battery cathode material. The difference between this comparative example and Example 1 is that the lithium iron phosphate substrate is not coated, steps two and three in Example 1 are omitted, and the preparation method is step one of Example 1.

[0088] The test results showed that the resistivity of the positive electrode material in Comparative Example 1 was 2202.50 Ω·cm.

[0089] Comparative Example 2 Comparative Example 2 provides a lithium-ion battery cathode material. The difference between this comparative example and Example 9 is that the lithium manganese iron phosphate matrix is ​​not coated.

[0090] Comparative Example 3 Comparative Example 3 provides a lithium-ion battery cathode material. The difference between this comparative example and Example 1 is that the lithium iron phosphate matrix is ​​only coated with the conjugated conductive polymer CPVC to prepare CPVC@LiFePO4. The preparation method is the same as steps one and two of Example 1, with step three omitted.

[0091] The test results showed that the resistivity of the positive electrode material in Comparative Example 3 was 908.23 Ω·cm.

[0092] Comparative Example 4 Comparative Example 4 provides a lithium-ion battery cathode material, which differs from Example 1 in that the second coating layer only coats CoOOH, thus preparing CoOOH@CPVC@LiFePO4.

[0093] The preparation method of Comparative Example 4 is basically the same as that of Example 1, except that step three is adjusted to: coating CoOOH with a second coating layer to prepare the final product CoOOH@CPVC@LiFePO4. The CPVC@LiFePO4 intermediate obtained in step two is mixed with nano-sized pure-phase CoOOH at a Co element content of 0.4% of the lithium iron phosphate mass. The mixture is stirred at 2000 rpm for 30 min using a high-speed mixer to ensure uniform dispersion of CoOOH on the surface of the intermediate. The mixed powder is then heated to 150°C at a heating rate of 5°C / min under a nitrogen atmosphere and held at this temperature for 1.5 h to obtain the final product, CoOOH@CPVC@LiFePO4 cathode material.

[0094] Comparative Example 5 Comparative Example 5 provides a lithium-ion battery cathode material, which differs from Example 1 in that: the second coating layer only coats single-phase Co3O4, and the cathode material is Co3O4@CPVC@LiFePO4.

[0095] The preparation method of Comparative Example 5 is basically the same as that of Example 1, except that step three is adjusted to: coating Co3O4 with a second coating layer to prepare the final product Co3O4@CPVC@LiFePO4. The CPVC@LiFePO4 intermediate obtained in step two is mixed with nano-sized Co3O4 powder at a Co element content of 0.4% of the lithium iron phosphate mass. The mixture is stirred at 2000 rpm for 30 min using a high-speed mixer and loaded onto the surface of the intermediate. The mixed powder is heated to 300℃ in air at a heating rate of 5℃ / min and held at that temperature for 3 h to obtain the final product, Co3O4@CPVC@LiFePO4 cathode material.

[0096] Comparative Example 6 Comparative Example 6 provides a lithium-ion battery cathode material. The difference between this comparative example and Example 10 is that the lithium iron phosphate matrix is ​​only coated with CoOOH / Co3O4 to prepare CoOOH / Co3O4@LiFePO4. The preparation method is the same as steps one and two of Example 10, with step three omitted.

[0097] The test results showed that the resistivity of the positive electrode material in Comparative Example 6 was 186.72 Ω·cm.

[0098] The cathode materials prepared in the examples and comparative examples were subjected to BET, Dv50, XRD, SEM-EDS, powder resistivity, and compaction tests, as detailed below: 1. Specific surface area test: The specific surface area was determined by a fully automated nitrogen adsorption specific surface area analyzer, in accordance with the national standard GB / T19587-2017 "Determination of specific surface area of ​​solid substances by gas adsorption BET method".

[0099] 2. Compacted density test: The compacted density tester of Sansi Zongheng UIM 7305 was used. The test method is as follows: Weigh 1g of the material to be tested and place it in a clean mold with a hole diameter of 13mm. Then place the mold on the pressure plate of the equipment and select a test pressure of 3T for testing.

[0100] 3. Test method for particle size Dv50 and Span: The particle size was determined using a laser particle size analyzer (instrument model: Mastersizer3000) in accordance with the national standard GB / T 19077-2024 Particle size analysis by laser diffraction; Span = (Dv90-Dv10) / Dv50.

[0101] 4. XRD was measured using an X-ray diffractometer, specifically the Rigaku Ultima IV X-ray diffractometer from Japan. The test parameters were: Cu target + monochromator, 40 kV / 40 mA, scanning range of 10-80°, step size of 0.02°, and scanning rate of 5° / min.

[0102] 5. Powder Resistivity Testing: Using a Yuaneng Technology powder resistivity tester, the positive electrode powder to be tested was placed in the sample chamber, and a constant axial pressure of 30 MPa was applied to compress the powder into a dense powder sheet. The resistivity of the compacted powder was measured using the four-probe method. The test environment was 25℃ and the relative humidity was 45%. 55%, the powder sample was pre-dried at 120℃ for 2 hours to remove adsorbed water.

[0103] 6. SEM-EDS: The microstructure and coating state of the particles were observed after the samples were sputter-coated with gold, and the elemental distribution was characterized by EDS element mapping.

[0104] The test results are shown in Table 1.

[0105] Table 1. Test results of Examples 1-10 and Comparative Examples 1-6

[0106] Lithium-ion coin cell battery preparation: The positive electrode material prepared in the above examples and comparative examples is mixed with conductive agent SP (conductive carbon black) and binder PVDF (polyvinylidene fluoride) at a mass ratio of 90:5:5, stirred evenly in NMP solvent, and then coated onto aluminum foil. After baking, rolling, and slicing, the positive electrode sheet is formed. Finally, the positive electrode sheet is assembled with a separator, lithium foil, and spacers to form a lithium-ion coin cell battery.

[0107] The fabricated lithium-ion button cells were tested using a battery testing cabinet. Test conditions were: voltage range 2.0-3.75V, test temperature 25±1℃. The specific charge / discharge procedure was as follows: first, allow to stand for 3 hours; then charge at 0.1C constant current to 3.75V, followed by constant voltage charging to 3.75V with a current limit of 0.05mA; allow to stand for 5 minutes, then discharge at 0.1C constant current to 2.0V; allow to stand for another 5 minutes, then charge at 1C constant current to 3.75V, followed by constant voltage charging to 3.75V (cutoff current 0.05mA); allow to stand for 5 minutes, then discharge at 1C constant current to 2.0V, and finally allow to stand for 5 minutes to complete the test. Data was collected at 10-second intervals throughout the entire process, and the nominal specific capacity was 160mAh g. -1 .

[0108] Since the substrate in Example 9 was adjusted to lithium manganese iron phosphate, its charge-discharge curve differed from that of lithium iron phosphate. Accordingly, the lithium-ion coin cell test conditions were adjusted to: a voltage range of 2.0-4.5V and a test temperature of 25±1℃. The specific charge-discharge regime was as follows: first, allow the cell to stand for 8 hours; then charge at a constant current of 0.1C to 4.5V, followed by constant voltage charging at 4.5V with a current limit of 0.05mA; allow the cell to stand for 5 minutes, then discharge at a constant current of 0.1C to 2.0V; allow the cell to stand for another 5 minutes, then charge at a constant current of 0.5C to 4.5V, followed by constant voltage charging at 4.5V (cutoff current 0.05mA); allow the cell to stand for 5 minutes, then discharge at a constant current of 1C to 2.0V; finally, allow the cell to stand for 5 minutes to complete the test, and the nominal specific capacity is 145mAh g. -1 .

[0109] The electrochemical performance test results of the coin cells in Examples 1-10 and Comparative Examples 1-6 are shown in Table 2.

[0110] Table 2. Electrochemical performance results of Examples 1-10 and Comparative Examples 1-6.

[0111] Preparation of lithium-ion full batteries: The positive electrode materials prepared in Examples 1 and Comparative Examples 3-4 were mixed with conductive agent (SP) and binder (PVDF) in NMP solvent at a mass ratio of 90:5:5 and coated onto aluminum foil current collectors. The positive electrode sheets were then baked, rolled, and sliced ​​to form positive electrode sheets. Graphite was used as the negative electrode active material and mixed with conductive agent (SP, CNT) and binder (CMC, SBR) in deionized water at a mass ratio of 94:2:4. The graphite was then coated onto copper foil current collectors and baked, rolled, and sliced ​​to form negative electrode sheets. The positive electrode sheets, separator, and negative electrode sheets were stacked in sequence and then installed into a battery casing. Electrolyte was injected and the casing was sealed. The electrolyte contained lithium salt and organic solvent. The lithium salt was LiPF6, and the organic solvent was a compound carbonate system of EC / DMC / EMC. The lithium salt concentration was 1.2 mol / L. The resulting lithium-ion full batteries were assembled.

[0112] The battery performance was tested using a battery test cabinet under the following conditions: voltage range 2.0–3.65 V, test temperature 25±1℃. After starting the test, the battery was allowed to stand for 5 minutes; then it was charged at a constant current of 3000 mA to 3.65 V, followed by constant voltage charging at 3.65 V until the current dropped to 300 mA; after charging, the battery was allowed to stand for 5 minutes, followed by constant current discharge at 3000 mA to 2.0 V, and then allowed to stand for 5 minutes. This charge-discharge process was counted as one complete cycle. The cycle was repeated until a total of 2000 cycles were reached, at which point the test was terminated. Data was recorded at 1-minute intervals throughout the test.

[0113] The electrochemical performance test results of the full cells of Example 1 and Comparative Examples 3-4 are shown in Table 3.

[0114] Table 3. Electrochemical performance results of the full cells in Example 1 and Comparative Examples 3-4

[0115] As shown in Tables 1 and 2, the olivine-type phosphate cathode materials based on the conjugated conductive polymer and cobalt-based dual-phase composite coating of the present invention, the cathode materials of Examples 1-10 generally have high compaction density, low powder resistivity, high capacity and rate performance.

[0116] As can be seen from Table 3, Example 1 is superior to Comparative Examples 3-4 in both 800th capacity retention and 800th discharge energy, demonstrating better cycle stability.

[0117] Depend on Figure 7 As can be seen, the full cell of Example 1 retains more than 88% of its capacity after 800 cycles, which is significantly better than that of Comparative Examples 3 and 4. Its cycle curve shows a smooth decay with no obvious accelerated degradation, indicating that the coated cathode material of the present invention can effectively suppress Fe dissolution and electrolyte side reactions, and significantly improve the long-term cycle stability of the material.

[0118] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.

[0119] Furthermore, those skilled in the art will understand that although some embodiments herein include certain features included in other embodiments but not others, combinations of features from different embodiments are intended to be within the scope of this application and form different embodiments. For example, in the foregoing claims, any of the claimed embodiments can be used in any combination. The information disclosed in this background section is intended only to enhance the understanding of the general background of this application and should not be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.

Claims

1. A lithium-ion battery cathode material, characterized in that, The lithium-ion battery cathode material includes a core and a first coating layer and a second coating layer that at least partially cover the core; The core includes a lithium phosphate cathode material; The first coating layer and the second coating layer are independently selected from conjugated conductive polymers or cobalt-containing materials, and the materials of the first coating layer and the second coating layer are different. The cobalt-containing material includes cobalt oxides and cobalt hydroxy compounds.

2. The lithium-ion battery cathode material according to claim 1, characterized in that, The general chemical formula of the lithium phosphate cathode material is LiFe. 1-x-y Mn x M y PO4, wherein 0 ≤ x ≤ 0.8, 0 ≤ y ≤ 0.15, and 1 - xy > 0; M includes at least one of Mg, Al, Ti, Zr, Ni, Co, Nb, and V; And / or, the conjugated conductive polymer includes at least one of polypyrrole, polyaniline, polythiophene, polycarbazole, and conjugated polyvinyl chloride; And / or, the cobalt oxide includes at least one of Co3O4 and CoO; And / or, the cobalt hydroxyl compound includes at least one of CoOOH and Co(OH)2; And / or, the mass of the conjugated conductive polymer accounts for 1.0% to 2.0% of the mass of the core; And / or, the mass of cobalt in the cobalt-containing material accounts for 0.2% to 0.6% of the mass of the core; And / or, the particle size of the kernel is 0.1~4.5μm.

3. The lithium-ion battery cathode material according to claim 1 or 2, characterized in that, The BET of the lithium-ion battery cathode material is 8-30 m. 2 / g; And / or, the compaction density of the lithium-ion battery cathode material is 2.1-2.56 g / cm³. 3 ; And / or, the powder resistivity of the lithium-ion battery cathode material is 10-300 Ω·cm; And / or, the Dv50 of the lithium-ion battery cathode material is 0.1~5.0 μm; And / or, the Span of the lithium-ion battery cathode material is 1.0-7.

0.

4. A method for preparing a lithium-ion battery cathode material, characterized in that, include: Provide a lithium phosphate cathode material matrix; The lithium phosphate cathode material matrix is ​​mixed with a first coating agent and subjected to a first sintering to obtain an intermediate. The intermediate is mixed with the second coating agent and subjected to a second sintering to obtain the lithium-ion battery cathode material. Wherein, the first coating agent and the second coating agent are independently selected from polymer precursors or cobalt-containing precursors, and the first coating agent and the second coating agent are different; The cobalt-containing precursor includes Co(OH)2, or a mixture of cobalt oxide and CoOOH, wherein the cobalt oxide includes at least one of Co3O4 and CoO.

5. The method for preparing the lithium-ion battery cathode material according to claim 4, characterized in that, The polymer precursor accounts for 1.0% to 2.0% of the mass of the lithium phosphate cathode material matrix; And / or, the mass percentage of cobalt in the cobalt-containing precursor is 0.2% to 0.6% of the mass of the lithium phosphate cathode material matrix; And / or, the polymer precursor includes polyvinyl chloride; And / or, the polymer precursor includes at least one of pyrrole, aniline, thiophene, and carbazole.

6. The method for preparing the lithium-ion battery cathode material according to claim 4, characterized in that, The preparation method satisfies at least one of the following conditions: A. When the first coating agent or the second coating agent is a polymer precursor, the preparation method includes: The polymer precursor is mixed with a solvent to obtain a solution containing the polymer precursor; The solution containing the polymer precursor is mixed with the lithium phosphate cathode material matrix or the intermediate and then dried, subjected to a first sintering or a second sintering to obtain an intermediate or lithium-ion battery cathode material with a polymer coating on its surface; optionally, the first sintering or the second sintering includes: raising the temperature to 200-400°C at a rate of 2-10°C / min and holding it at that temperature for 4-10 hours. B. When the first coating agent or the second coating agent is a polymer precursor, the preparation method includes: The polymer precursor is mixed with an initiator, the lithium phosphate cathode material matrix or the intermediate, and an in-situ polymerization reaction is carried out to form a polymer reactant. The polymer reactants are washed, dried, and then subjected to a first sintering or a second sintering to obtain an intermediate or lithium-ion battery cathode material with a polymer coating on its surface; optionally, the first sintering or the second sintering includes: raising the temperature to 200-400°C at a rate of 2-10°C / min and holding it at that temperature for 4-10 hours. C. When the first coating agent or the second coating agent is Co(OH)2, the first sintering or the second sintering includes: raising the temperature to 130℃~250℃ at a heating rate of 2~5℃ / min and holding it at that temperature for 1~2h; then raising the temperature to 250℃~400℃ at a heating rate of 2~5℃ / min and holding it at that temperature for 2~4h. D. When the first coating agent or the second coating agent is a mixture of cobalt oxide and CoOOH, the first sintering or the second sintering includes: raising the temperature to 200-250°C at a heating rate of 2-5°C / min, holding at the temperature for 2-4 h, and the mass ratio of cobalt oxide to CoOOH is (0.4~2.0):

1.

7. The method for preparing the lithium-ion battery cathode material according to claim 6, characterized in that, The solvent includes at least one of tetrahydrofuran, dimethyl sulfoxide, cyclohexanone, dimethylformamide, methyl isobutyl ketone, and N-methylpyrrolidone; And / or, the pH of the system is 1 to 3 when the in-situ polymerization reaction is carried out; And / or, the initiator includes at least one of ammonium persulfate, potassium persulfate, and sodium persulfate; And / or, the mass ratio of the initiator to the polymer precursor is (0.3~1.2):1; And / or, the in-situ polymerization reaction is carried out at a temperature of 5-35°C for a time of 2-7 hours.

8. The method for preparing the lithium-ion battery cathode material according to any one of claims 4-7, characterized in that, The method for preparing the lithium phosphate cathode material matrix includes: A slurry is obtained by mixing lithium source, iron source, phosphorus source, carbon source and water; The slurry was spray-dried to obtain precursor powder; The precursor powder is subjected to a third sintering process to obtain a lithium phosphate cathode material matrix.

9. The method for preparing the lithium-ion battery cathode material according to claim 8, characterized in that, The method for preparing the lithium phosphate cathode material matrix satisfies at least one of the following conditions: (1) The lithium source includes at least one of lithium carbonate, lithium dihydrogen phosphate, and lithium hydroxide; (2) The iron source includes at least one of ferric phosphate, ferric manganese phosphate, ferrous oxalate, ferric oxide, ferrous sulfate, and ferric nitrate; (3) The phosphorus source includes at least one of iron phosphate, lithium dihydrogen phosphate, ammonium dihydrogen phosphate, and phosphoric acid; (4) The carbon source includes at least one of glucose, polyethylene glycol, sucrose, and citric acid; (5) The mass of the carbon source accounts for 5-16% of the total mass of the iron source and the phosphorus source; (6) The D50 of the slurry is 0.3~2.5μm; (7) The inlet air temperature of the spray dryer is 230-270℃ and the outlet air temperature is 90-110℃; (8) The third sintering is carried out under nitrogen protection, and the third sintering includes: raising the temperature to 650~820℃ at a heating rate of 1~5℃ / min and holding it for 6~15h; (9) The slurry further includes a manganese source, wherein the manganese source is selected from at least one of manganese ferric phosphate, manganese dioxide, manganese tetroxide, manganese phosphate, and manganese carbonate; (10) The slurry further includes an M source, which includes at least one of Mg source, Al source, Ti source, Zr source, Ni source, Co source, Nb source and V source.

10. A lithium-ion battery, characterized in that, It includes the lithium-ion battery cathode material according to any one of claims 1-3 or the lithium-ion battery cathode material prepared by the preparation method according to any one of claims 4-9.